PENGARUH BAURAN PROMOSI TERHADAP PENJUALAN HASIL LAUT PADA PT. NAPUCINTA MAKASSAR - Agus, Rosida Maedina (Jurnal Unicorn ADPERTISI, 2022)
This study aims to determine the promotion mix, namely personal selling has an effect on the sale of marine products at PT. Napucinta Makassar and to find out the promotion mix, namely the promotion effect on the sale of marine products at PT. Napucinta Makassar. This research is an explanatory research, because this research explains the causal relationship between variables through hypothesis testing. Data analysis using multiple linear regression analysis. The results of the study show that personal selling has a positive effect on sales, which means that the better the interactions and services provided by the company. Sales promotions affect a positive sales.